Pengembangan E-LKPD Berbasis Liveworksheets untuk Meningkatkan Kemampuan Scientific Reasoning Peserta Didik SMP - Deska Mayangsari; Guntur Cahaya Kusuma; Rahma Diani (WISE Pendidikan Indonesia, 2026)
This study aims to develop and evaluate Liveworksheets-based electronic student worksheets (E-LKPD) designed to strengthen junior high school students' scientific reasoning in the topic of motion and force. The study was motivated by needs-analysis findings indicating that science learning in three schools in Bandar Lampung still relied heavily on static printed worksheets and teacher-centered explanation, limiting students' opportunities to formulate hypotheses, interpret evidence, and justify conclusions. The research employed a research-and-development design adapted from Borg and Gall, limited to seven stages: potential and problem analysis, data collection, product design, design validation, design revision, limited product testing, and final product revision. The product was validated by material and media experts and tested with 70 students and science teachers from SMP Negeri 5 Bandar Lampung, MTs Negeri 2 Bandar Lampung, and MTs Masyariqul Anwar. The results showed that the E-LKPD was highly valid according to material experts (91.25%) and media experts (93.10%). Teacher responses reached 92.45% in the very practical category, while student responses reached 90.78% in the very attractive category. The scientific reasoning-oriented tasks were rated strongest in evidence-based conclusion-making and data interpretation. These findings indicate that Liveworksheets-based E-LKPD is feasible, practical, and attractive as a digital science learning resource that scaffolds scientific reasoning through interactive worksheets, multimedia prompts, and automatic feedback. The study contributes to technology-integrated science worksheet development for lower secondary education.